AN ANALYSIS OF THE IMPLEMENTATION OF PEER CORRECTION TECHNIQUE ON STUDENTSâ EXPOSITION TEXT - Rachmawati, Dina; Juniardi, Yudi; Fauziah, Zahra (Research And Innovation In Language Learning (RILL), 2018)
This research aimed to: 1) analyze quality of studentsâ exposition text; 2) analyze their responses towards learning writing exposition text using peer correction technique; and 3) find out challenges that they faced during the learning. Qualitative research method, especially document analysis design, was chosen. In this research, studentsâ texts were analyzed to answer first research question and open-ended questionnaire was given to students to answer second and third research questions. To triangulate the findings from those instruments, peer debriefing and member checks methods were done. To analyze the data, qualitative data analysis by Miles et al. (2014) was employed. The data analysis revealed that: 1) quality of studentsâ exposition texts improved, especially in generic structure aspect; 2) students mostly grouped themselves with more competent peers, learned lesson material beforehand as preparation for correcting, used both English and Indonesian when correcting, concerned more about language feature of peersâ texts, employed their critical thinking in processing feedbacks, became a better writer in the end of semester, and still preferred teacher correction over peer correction technique; and 3) students biggest challenge was poor writing skill. From those findings, it is highly recommended that teachers who want to apply this technique should thoughtfully group the students by themselves and give any assistance needed by students as probably their writing skill may impede them in giving meaningful feedback.Â